2009
DOI: 10.1007/s10641-009-9447-x
|View full text |Cite
|
Sign up to set email alerts
|

Age and growth analysis of the shortfin mako, Isurus oxyrinchus, in the western and central North Pacific Ocean

Abstract: We determined the age and growth rates of male and female shortfin makos, (Isurus oxyrinchus), from the western and central North Pacific Ocean. Growth band pairs were counted on half-cut vertebral centra using a shadowing method. In this method, we focused on the ridges on the surface of the centra, consisting of a convex and concave structure. After comparing four enhancing methods, we decided on the use of shadowing method for aging. Vertebrae from 128 males and 147 females were examined. The centrum edge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
50
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 33 publications
9
50
1
Order By: Relevance
“…Campana et al 2005;Bishop et al 2006;Natanson et al 2006;Cerna and Licandeo 2009;Semba et al 2009). determined the ages of 44 samples from the eastern Pacific using whole vertebral centra with x-radiography and validated with modal progression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Campana et al 2005;Bishop et al 2006;Natanson et al 2006;Cerna and Licandeo 2009;Semba et al 2009). determined the ages of 44 samples from the eastern Pacific using whole vertebral centra with x-radiography and validated with modal progression analysis.…”
Section: Introductionmentioning
confidence: 99%
“…There is a large sexual difference in the size and age at maturity, with males maturing at about 195 cm total length (L T ) at 6 years of age, and females at 265-280 cm L T at 16 years of age (Stevens, 2008;Semba et al, 2009). While segregation among the developmental stages (Nakano and Nagasawa, 1996) and geographical sexual segregation (Mucientes et al, 2009) have been reported, little is known about stock structure or genetic diversity (Heist et al, 1996) due to the species' large, diffuse, and highly dispersive populations (Schrey et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, using the whole centrum has the advantage that the entire surface of the corpus calcareum is available for examination. Semba et al (2009) used this whole centrum technique and observed uneven annuli on the surface of the corpus calcareum in the short-fin mako, Isurus oxyrinchus, using the shadowing method. Therefore, we examined only the corpus calcareum using X-radiography to compare the visibility of growth bands with the previous studies of the white shark.…”
Section: Introductionmentioning
confidence: 99%